Socio-emotional correlates of a schooldog-teacher-team in the classroom - Beetz, Andrea (Frontiers in Psychology, 2013)
A growing number of teachers in Europe regularly take their dogs with them into the classroom. Limited research points at positive socio-emotional effects of this practice. In this study the effects of a schooldog-teacher-team on socioemotional experiences in school, depression and emotion regulation strategies were investigated in a classroom of third-graders (male n = 12, female n = 13), which had a schooldog present for 1 day per week in comparison with a control class (male n = 11, female n = 10). In contrast to the control class, the dog-class students reported a stronger improvement with regard to positive attitude toward school (repeated measures ANOVA; F = 10.769, df = 1, p = 0.002) and positive emotions related to learning (F = 4.479, df = 1, p = 0.042) over the course of the year. Since a prerequisite of all kinds of effective learning is a positive attitude and mood toward school and learning, the presence of a schooldog-teacher team thus has the potential to support learning.